2013
DOI: 10.1055/s-0033-1354366
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like Property of Jobelyn®, an African Unique Herbal Formulation, in Mice

Abstract: Jobelyn® has antidepressant-like activity, which may be related to the stimulation of serotonergic and noradrenergic pathways. The ability of Jobelyn® to delay the onset of immobility and to prolong the struggling time support its use as energizer in general body weakness or exhaustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Moreover, JB has gained international recognition as a remedy for treatment of anaemia, arthritic pains and relief of stress [17]. We have previously reported that JB exhibited anti-depressant and anti-amnesic properties in rodents [18] [19]. In this present study, we report on the effect of Jobelyn ® on unpredictable chronic mild stress-induced memory impairment in mice.…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, JB has gained international recognition as a remedy for treatment of anaemia, arthritic pains and relief of stress [17]. We have previously reported that JB exhibited anti-depressant and anti-amnesic properties in rodents [18] [19]. In this present study, we report on the effect of Jobelyn ® on unpredictable chronic mild stress-induced memory impairment in mice.…”
Section: Introductionmentioning
confidence: 65%
“…This is especially important in a developing African context, where the high cost of conventional therapies hinders drug compliance and contributes to disease-related morbidity and mortality. The results from such clinical trials are necessary, as they are expected to provide the evidential strength that researchers need to significantly reduce some of the barriers to the clinical adoption of validated indigenous phytomedicines [121] in mainstream medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability of SBSJ to reduce corticosterone is an important finding from the study of Umukoro et al [120]. The possibility of SBSJ behaving like an adaptogen is also based on findings that it attenuated depression-like symptoms in mice subjected to stressful situations (i.e., forced swimming exercise and tail suspension protocols) [121]. In an in vitro stress model, it has also been reported that SBSJ protected RBCs against hyposaline-induced haemolysis [43], suggesting cyto-protection and increased cellular resistance to stress.…”
Section: Sbsj As An Adaptogenmentioning
confidence: 99%
“…In the same study, interferon-alpha (IFN-), an antiviral cytokine showed increased expression by 12-fold following treatment with SBLS extract. 29 There seems to be a correlation between high IFN-production capacities and low HIV viral loads as well as high CD4 cell counts and lack of opportunistic infections. 30,31 This effect can be related to the direct anti-viral role of IFN-on infected HIV cells.…”
Section: Anti-inflammatory Effects Of the Sbls Extracts On Cytokines mentioning
confidence: 99%